2022
DOI: 10.3390/ijerph19159332
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Job Satisfaction of Caregivers in a Home-Based Elderly Care Program

Abstract: Population aging has increased the demand for elderly care worldwide. The home-based elderly care system plays an important role in meeting this demand in developing countries. The quality of home-based elderly care is associated with the job satisfaction of caregivers in home-based elderly care programs, which has rarely been studied. This paper explores the factors that affect the job satisfaction of these elderly caregivers, including personal characteristics, working conditions, employment status, training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…More than half of these workers are engaged on an hourly schedule, but some still work as live-in workers. Coinciding with the findings of previous studies, most home care workers in Shanghai lack labor contracts [ 10 , 11 ]. Most of them are rural married migrant women who work in the informal sector and have a low level of education.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…More than half of these workers are engaged on an hourly schedule, but some still work as live-in workers. Coinciding with the findings of previous studies, most home care workers in Shanghai lack labor contracts [ 10 , 11 ]. Most of them are rural married migrant women who work in the informal sector and have a low level of education.…”
Section: Discussionsupporting
confidence: 83%
“…They are mainly middle-aged and low-educated. A large-scale random-sample survey of domestic workers conducted in 2019 revealed that only 1.6% of care workers in Beijing have labor contracts [ 10 , 11 ]. Other studies show that these female rural migrant care workers usually work overtime, lack leisure time, and sometimes have to face abuse from clients [ 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, working under time pressure might lead to poorer quality of care in a form of providing only basic care, instead of holistic care [ 47 ]. Previous studies among staff working in home care services have similarly highlighted the relation to clients as a factor influencing job satisfaction [ 48 ] and lack of control, role conflicts and role overload as factors influencing stress [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…When a nurse is making crucial clinical decisions and implementing evidence-based practices, emotional intelligence plays a significant role and has a significant impact on their clinical life. On the other hand, their level of job satisfaction was strongly impacted by stress at work, rising hospital nurse demands for daily tasks, and increased accountability for their work 1,2 .…”
Section: Introductionmentioning
confidence: 99%